The limits of culture : Islam and foreign policy - Shaffer, Brenda (BCSIA studies in international security., 2006)
"The Limits of Culture explores the effect of culture on foreign policy, focusing on countries in the geopolitically important Caspian region and paying particular attention to those states that have identified themselves as Islamic republics: Iran, Taliban Afghanistan, and Pakistan."--Jacket.